Prediction of high thermoelectric performance in the low-dimensional metal halide Cs3Cu2I5 - Young-Kwang Jung (Nature Portfolio, 2021)
Abstract Metal halides have emerged as a new generation of semiconductors with applications ranging from solar cells to chemical sensors. We assess the thermoelectric potential of Cs3Cu2I5, which has a crystal structure formed of zero-dimensional [Cu2I5]3− anionic clusters that are separated by Cs+ counter cations. We find the compound exhibits the characteristics of a phonon-glass electron-crystal with a large imbalance in the conduction of heat and electrons predicted from first-principles transport theory. Strong anharmonic phonon–phonon scattering results in short-lived acoustic vibrations and an ultra-low lattice thermal conductivity (<0.1 W m−1 K−1). The dispersive conduction band leads to a high electron mobility (>10 cm2 V−1 s−1). For an n-type crystal at 600 K, a thermoelectric figure-of-merit Z T of 2.6 is found to be accessible, which for a cold source of 300 K corresponds to a thermodynamic heat-to-electricity conversion efficiency of 15%.